1977
DOI: 10.1111/j.1365-3091.1977.tb00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Chertification in the Mississippian Lake Valley Formation, Sacramento Mountains, New Mexico

Abstract: Chert distribution in the Lake Valley rocks is selective to mud‐supported facies; it is not related to proximity to unconformities. The facies selectivity of the chertification is believed to be a function of the depositional distribution of indigenous silica as sponge spicules, an interpretation that is supported by high positive qualitative correlation of chert with spiculitic rocks. Petrography indicates that the spicules were all originally siliceous, and that they all went through a moldic stage during wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
2

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 27 publications
6
54
0
2
Order By: Relevance
“…Possible sources of silica include remobilization from volcanic ash, clay minerals, hydrothermal groundwater, and meteoric water. Subaerial exposure may have created intake areas for circulation of silica-rich meteoric waters into the subsurface, a process that is 14 commonly invoked to explain silicification and karst features beneath unconformities in other carbonate successions (Meyers, 1977;Young et al, 2012). The silica casts were later exhumed during erosion that formed the unconformity, and reworked into the upper bioclastic member.…”
Section: Synthesis and Interpretation Southern Bouse Formationmentioning
confidence: 99%
“…Possible sources of silica include remobilization from volcanic ash, clay minerals, hydrothermal groundwater, and meteoric water. Subaerial exposure may have created intake areas for circulation of silica-rich meteoric waters into the subsurface, a process that is 14 commonly invoked to explain silicification and karst features beneath unconformities in other carbonate successions (Meyers, 1977;Young et al, 2012). The silica casts were later exhumed during erosion that formed the unconformity, and reworked into the upper bioclastic member.…”
Section: Synthesis and Interpretation Southern Bouse Formationmentioning
confidence: 99%
“…Although Lees and Miller (1995) stressed that the timing of silicification appears late and unrelated to the considerable amount of sponge-spicule silica, other studies (Meyers 1977;de Brit 1989;Butts and Briggs 2011) found a very similar spatial pattern of silicification that was related to early diagenetic stratigraphic trapping (off-mound chert, silicification of fossils on flanks or along coarse reef-talus deposits). Meyers (1977) andde Brit (1989) demonstrated that this pattern originated during early diagenesis of sediment burial at depths of a few meters to a few tens of meters.…”
Section: Patterns Of Silicification Timing Corrosion and Substratementioning
confidence: 92%
“…Bissell 1959;Cavoroc & Ferm 1968;Meyers 1977;Geeslin & Chafetz 1982;Maliva & Siever 1989;Carlson 1994;Ruppel & Hovorka 1995), including studies of Mississippian rocks in Kansas (Montgomery et al 1998;Watney et al 2001;Franseen 2006). The results presented herein also show an early diagenetic event of dissolution of sponge spicules (thereby leaving molds) and redistribution of silica as evidenced by silicification of original lime-mud material and calcitic fossils.…”
Section: Subaerial V Hydrothermal Porosity Enhancement In Chertmentioning
confidence: 95%